Carotid Adventitial Vasa Vasorum and Intima‐Media Thickness in a Primary Prevention Population. Issue 2 (13th June 2014) - Sampson, Uchechukwu K. A.; Harrell, Frank E.; Fazio, Sergio; Nwosu, Sam; Mercaldo, Nate; Mensah, George A.; Davidson, Michael H.; Coll, Blai; Feinstein, Steve B.
<x xml:space="preserve">Abstract</x> Background Vasa vasorum (VV) vessels are critical in the genesis of atherosclerosis. Therefore, we assessed measures of carotid VV, intima–media thickness (CIMT), and patient risk factors in a primary prevention population. Methods We used multivariable linear models to evaluate the relationship between baseline covariates and a measure of carotid VV (VV ratio) and CIMT among 324 diabetics and 141 nondiabetics. Results Median CIMT (in mm) and VV ratio among nondiabetics were 0.82 ± 0.22 and 0.80 ± 0.19, respectively, and 1.06 ± 0.19 and 1.21 ± 0.26 among diabetics (P < 0.0001). Diabetes was associated with 36% (95% CI: 24.3–48.0, P < 0.001) higher VV ratio whereas a unit change in BMI was associated with ≈1% (95% CI: 0.5–1.4, P < 0.001) change in VV ratio. A 10‐year increase in age was associated with 4% (95% CI: 1–7, P = 0.005) higher CIMT. Each 10 mmHg increase in mean systolic blood pressure was associated with 2% (95% CI: 1–4, P = 0.003) higher CIMT whereas diabetes conferred 31% (95% CI: 19.1–42.1, P < 0.001) higher CIMT. Female sex was associated with a 9% (95% CI: −12.9 to −4.1, P < 0.001) lower CIMT. Low density lipoprotein (LDL) cholesterol, blood pressure, and CIMT were not significantly associated with VV ratio. Conclusion In this cohort of patients with low CIMT, VV ratio, and CIMT were distinctly unrelated, but each independently associated with diabetes. VV ratio and CIMT relationships warrant further investigation in large‐scale studies and across a spectrum of atherosclerostic states.